Effects of Position-Switching Training on Muscular Strength and Technical Performance in U-20 Football Players: An Experimental Study - Rasheed, Abbas Majid; Rasheed, Mohanad Abdul-Qader; Abdulrazzaq Waheeb Yaseen (Pubmedia Jurnal Pendidikan Olahraga, 2026)
This study aimed to design and implement position-switching exercises and examine their effects on muscular strength and fundamental football skills among under-20 players. An experimental approach with a one-group pre-test-post-test design was adopted. The sample consisted of 12 players from Al-Sinaa Sports Club (Baghdad, Iraq). The training program lasted eight weeks (three sessions per week), incorporating structured position-switching drills within the main part of each. training session. The results revealed statistically significant improvements (p ≤ 0.05) in all physical and skill variables, including explosive power, speed-strength, strength endurance, passing accuracy, and dribbling performance. The magnitude of change across variables indicates a meaningful practical impact of the intervention. The study concludes that position-switching training represents an effective and practical method for developing youth football players, as it integrates physical and technical components within. realistic performance contexts.